Chiny - sukces gospodarczy a deficyty rozwojowe - Czech-Rogosz, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The image of modern China is ambivalent. It means economic success, that make people delighted from the one side, but there are also many development gaps that one has to pay attention to from the other side. The most important gaps are income differentiation, inhuman labour conditions, stealing of western know how and technologies, environmental exploitation and pollution. The purpose of the article is to point out China's economic growth circumstances and the most important development gaps which pose a threat for further social and economic development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 61-71